Real-time systems design and analysis : tools for the practitioner - Laplante, Phillip A.; Ovaska, Seppo J., 1956- (Hoboken, N.J. : Wiley-IEEE Press, 2012)
"An important resource, this book offers an introductory text and overview of real-time systems: systems where timeliness is a crucial part of the correctness of the system. The book contains a pragmatic overview of key topics (computer architecture and organization, operating systems, software engineering, programming languages, and compiler theory) from the perspective of the real-time systems designer. The book is organized into chapters that are essentially self-contained. Thus, the material can be rearranged or omitted depending on the background and interests of the audience or instructor. Each chapter contains both easy and more challenging exercises that stimulate the reader to confront actual problems"--
"The book contains a pragmatic overview of key topics (computer architecture and organization, operating systems, software engineering, programming languages, and compiler theory) from the perspective of the real-time systems designer. The book is organized into chapters that are essentially self-contained. Thus, the material can be rearranged or omitted depending on the background and interests of the audience or instructor. Each chapter contains both easy and more challenging exercises that stimulate the reader to confront actual problems"--
Includes bibliographic references and index.
Keywords: Real-time data processing; System design